Assessment of needlestick injuries and hepatitis B and C infection among surgeons - Mehrvarz, Shaban; Khatami, Seyed Masoud; Manoochehry, Shahram; Khedmat, Hossien; Arefinia, Mahdi; Rasouli, Hamid Reza (Universa Medicina, 2020)
BackgroundSpecialist surgeons are at high risk of exposure to hepatitis viruses through occupational exposure to blood or body fluids. Protective measures against occupational exposure to the hepatitis B virus (HBV) and hepatitis C virus (HCV) must be taken in order to prevent infection in surgeons. We aimed to determine the needlestick injuries, and markers HBV and HCV in Iranian surgeons.MethodsThis study was cross-sectional research, performed in Baqyatallah, Shohada, Rasoul Akram, Sina, Taleghani, and Emam Hossein hospitals (all university hospitals) of Tehran, Iran. Overall 318 eligible surgeons were included. Anonymous questionnaires were used containing data about demographic characteristics, self-reported blood and needlestick contacts, occasional exposures, risk behaviors and vaccination. Also, the blood samples were taken and tested for hepatitis B surface antigen (HBsAg), antibody against Hepatitis B surface antigen (antiHBs) and HCV antibody (HCVAb). Fisher exact test and Kruskal Wallis test were used to analyze the data.ResultsThe mean age of the surgeons was 47.76 ± 8.95 years and 177 of them (55.66%) were male. The average number of needle–sticks was 28.28 ± 16.58 during the surgeons’ working life. Among them, 5 cases (1.59%) were positive for HBsAg and 2 cases (0.66%) were positive for HCVAb. ConclusionIn spite of the high needlestick rate in Iranian surgeons, prevalence of hepatitis B and C is not very high among them. A high degree of vigilance and a careful surgical technique is the only means available to prevent the transmission of the viruses.